2016
DOI: 10.1037/apl0000059
|View full text |Cite
|
Sign up to set email alerts
|

Skewed task conflicts in teams: What happens when a few members see more conflict than the rest?

Abstract: Task conflict has been the subject of a long-standing debate in the literature-when does task conflict help or hurt team performance? We propose that this debate can be resolved by taking a more precise view of how task conflicts are perceived in teams. Specifically, we propose that in teams, when a few team members perceive a high level of task disagreement while a majority of others perceive low levels of task disagreement-that is, there is positively skewed task conflict, task conflict is most likely to liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 65 publications
2
54
2
Order By: Relevance
“…Specifically, we focus on the role of task conflict occurs in the vertical dyad of a supervisor and the subordinate (i.e., vertical task conflict) by developing and testing a model in which LMX attenuates vertical task conflict, which in turn affects employee creativity in a curvilinear fashion. In line with prior research on task conflict in groups (e.g., Jehn, ; Langfred, ; Sinha et al, ), we define vertical task conflict as disagreements in supervisor–subordinate dyads about opinions, ideas, viewpoints, and decisions. We choose to focus on vertical task conflict because conflict is ubiquitous in leader–follower interactions (Tushman, ), and research has suggested interpersonal relationships influence conflict (Paglis and Green, ), and conflict in turn influences the informational basis on which creativity emerges (Kurtzberg and Mueller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we focus on the role of task conflict occurs in the vertical dyad of a supervisor and the subordinate (i.e., vertical task conflict) by developing and testing a model in which LMX attenuates vertical task conflict, which in turn affects employee creativity in a curvilinear fashion. In line with prior research on task conflict in groups (e.g., Jehn, ; Langfred, ; Sinha et al, ), we define vertical task conflict as disagreements in supervisor–subordinate dyads about opinions, ideas, viewpoints, and decisions. We choose to focus on vertical task conflict because conflict is ubiquitous in leader–follower interactions (Tushman, ), and research has suggested interpersonal relationships influence conflict (Paglis and Green, ), and conflict in turn influences the informational basis on which creativity emerges (Kurtzberg and Mueller, ).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, whether a pattern of divergence is bimodal, driven by a minority, or broadly fragmented could have important theoretical implications for team process and effectiveness (DeRue et al, 2010). For example, Sinha and colleagues showed that the proportion of team members that perceive task conflict is important, finding a positive effect on performance when fewer members perceive task conflict ("positively skewed task conflict"; Sinha et al, 2016).…”
Section: Concordance Challenges In Studying Difference Factorsmentioning
confidence: 99%
“…Klein and Kozlowski (2000) differentiated between “shared team properties”—team-level properties such as perceptions of cohesion, which researchers expect team members to agree upon—versus “configural team properties” such as personality type, which researchers expect to vary among team members. More recently, researchers have found that even team properties often assumed to be shared among team members, such as perceptions of conflict, can vary greatly within a team (e.g., Jehn et al, 2010; Sinha et al, 2016). Moreover, these configurational and perceptual differences among team members may lead to “emergent diversity,” in which team processes become more diverse, instead of more similar, over time (Van Knippenberg & Mell, 2016).…”
Section: Factors Of Differencementioning
confidence: 99%
“…Low perceivers may not pick up on information that others experience a heightened level of conflict. Research on conflict asymmetry has found that high perceivers use more conciliatory conflict resolution strategies (De Dreu, Kluwer, & Nauta, 2008) and are more motivated to present their arguments in a careful and politically sensitive manner (Sinha et al, 2016) because they recognize their lack of power. In a nonhierarchical team setting, high perceivers recognize that they do not have more or less power than others to affect change and will, thus, want to present any divergent opinions in a noncombative manner.…”
Section: Individual Task Conflict Asymmetrymentioning
confidence: 99%
“…The basis for this reexamination is the acknowledgment that consensus may more often be the exception than the norm and that valuable insights on team-level outcomes can be gained by examining patterns of dissensus (Klein & Kozlowski, 2000). To this end, researchers have examined how various patterns of dissensus, such as uniform (Jehn, Rispens, & Thatcher, 2010) and nonuniform (Sinha, Janardhanan, Greer, Conlon, & Edwards, 2016) distributions of task conflict perceptions at the team level influence team outcomes.…”
mentioning
confidence: 99%